2010
DOI: 10.1245/s10434-010-1371-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Survivin Gene Promoter Polymorphism (−31G>C) in Susceptibility and Survival of Esophageal Cancer in Northern India

Abstract: Survivin promoter region polymorphism (-31G>C) is associated with susceptibility and clinical characteristics but not prognosis of esophageal cancer in northern Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
3
36
1
Order By: Relevance
“…Jaiswal et al (2011) have determined carrying homozygous C allele for -31 G/C polymorphism increases 2.6 fold risk of bladder cancer. Also, homozygous C allele for survivin -31 C/G has been shown that increased cancer risk in urothelial cancer (Wang et al, 2009), bladder cancer (Kawata et al, 2011), nasopharyngeal carcinoma (Ma et al, 2011), esophagus cancer (Upadhyay et al, 2011), prostate cancer (Chen et al, 2013) and colorectal cancer (Gazouli et al, 2009; studies. Yazdani et al (2012) also have demonstrated that GC and CC genotype distributions of survivin -31 G/C polymorphism were found statistically significant differences between thyroid cancer patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Jaiswal et al (2011) have determined carrying homozygous C allele for -31 G/C polymorphism increases 2.6 fold risk of bladder cancer. Also, homozygous C allele for survivin -31 C/G has been shown that increased cancer risk in urothelial cancer (Wang et al, 2009), bladder cancer (Kawata et al, 2011), nasopharyngeal carcinoma (Ma et al, 2011), esophagus cancer (Upadhyay et al, 2011), prostate cancer (Chen et al, 2013) and colorectal cancer (Gazouli et al, 2009; studies. Yazdani et al (2012) also have demonstrated that GC and CC genotype distributions of survivin -31 G/C polymorphism were found statistically significant differences between thyroid cancer patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is highly expressed in various human malignancies, but its expression is very low or below the level of detection in normal adult tissues (Ambrosini et al, 1998;Yazdani et al, 2012). Survivin is usually expressed in the G 2 /M phase of the cell cycle, when it is thought to disrupt the apoptosis signaling pathways and to promote the survival of abnormal cells, offering a significant advantage to tumor cells overexpressing survivin (Upadhyay et al, 2011). The elevated expression of survivin is thought to be a negative prognostic factor for tumors and its overexpression is reported to be associated with shortened survival (Altieri, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Clarification of the survivin signaling pathway will provide new predictive and prognostic information for cancer diagnosis and could lead to the development of new therapeutic alternatives for a variety of cancers (Altieri, 2001;Yamamoto and Tanigawa, 2001). High survivin expression has been detected in several cancer types in humans, including colorectal cancer, hepatocellular cancer, lung cancer, pancreatic cancer, and osteosarcoma (Wang et al, 2009;Yang et al, 2009;Theodoropoulos et al, 2010;Upadhyay et al, 2011; Borges et al, 2011;Srivastava et al, 2012). Survivin is also expressed in breast cancer (Yamashita et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Following this finding, researchers used in vitro promoter assays to demonstrate that the À31G allele had significantly lower transcriptional activity than the À31C allele, suggesting that the À31G/C polymorphism influences survivin expression, thus contributing to the genetic susceptibility to lung cancer. 13 Recently, many studies have investigated the role of the survivin À31G4C polymorphism in the etiology of various type of cancers, [13][14][15][16][17][18][19][20][21][22][23][24][25] including lung, gastric, bladder, esophageal, colorectal, urothelial, and pancreatic cancer. However, the results of these studies remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%